Development of Spray Made From Kelakai Leaves (Stenochlaena palustris) and Effectiveness in the Healing of Perineal Wounds - Ida Ayu Oktari; Krisdiana Wijayanti; M. Choiroel Anwar (JURNAL INFO KESEHATAN, 2025)
The prognosis or possible diagnosis in postpartum mothers with perineal suture wounds is the possibility of infection of perenium suture wounds. Kelakai leaf plants are plants that contain flavonoids, tannins, saponins, alkaloids, and tripenoids. This study aims to innovate and develop perineal wound medicine using kelakai leaf spray and analyze its effectiveness based on REEDA scale indicators (redness,edema, ecchymosis, discharge, approximation). This study uses a quantitative method with a Reseach and development approach. The sampling technique uses non-probability sampling with a type of purposive sampling selecting 34 respondents, who are divided directly between the two groups. The intervention group received treatment of perineal wounds for 7 days with kelakai leaf spray and education on how to treat perineal wounds, while the control group received treatment with placebo spray and education on how to treat perineal wounds. The spray is administered four times a day with a dose of four sprays. Wound healing was measured by the REEDA Scale on days 3, 5, and 7. A tool to measure hb levels with digital hb, to measure protein intake, calorie intake, and fe intake using food recall. Data analysis includes Friedman and Mann Whitney as well as Stratification. The results showed that there was a difference in the average healing of perineal wounds at the observation time between the intervention group and the control group (p=0.000). On average, the difference in perineal wound healing using the REEDA scale showed a significant difference between the intervention group and the control group (p=0.000). A value of 3.2 is considered a relatively large measure of effect. The irritation test obtained results that did not cause irritation, In conclusion, the developed Kelakai leaf spray was effective in helping to accelerate the healing of perineal wounds, as evidenced by the difference in the mean healing time of perineal wounds with the SIGINFIC REEDA scale in postpartum mothers in the intervention group compared to the control group (p=0.000).